<span>When the product of two numbers is one</span>
They both have the same rate of change
The answer is <span>2(–4y + 13) – 3y = –29
Step 1: Express </span><span>x from the second equation
Step 2: Substitute x into the first equation:
The system of equations is:
</span><span>2x – 3y = –29
x + 4y = 13
Step 1:
</span>The second equation is: x + 4y = 13
Rearrange it to get x: x = - 4y + 13
Step 2:
The first equation is: 2x – 3y = –29
The second equation is: x = - 4y + 13
Substitute x from the second equation into the first one:
2(-4y + 13) - 3y = -29
Therefore, the second choice is correct.
Answer:
(10; -1)
the x-coordinate of the other endpoint is (x;y)
because the segment has midpoint at (3;0)
=> x - 4 = 3.2 = 6
y + 1 = 0.2 = 0
<=> x = 10
y = -1
=> the other endpoint is (10; -1)